Antiobesity effect of Bauhinia variegata bark extract on female rats fed on hypercaloric diet - Gunasekaran Balamurugan; Palayan Muralidharan (Bangladesh Pharmacological Society, 2010)
The present study was carried out toinvestigate the antiobesity effect of methanolic extract of stem and root barks of Bauhinia variegata Linn in female rats fed with hypercaloricdiet. Obesity was induced by administration of hypercaloric diet for 40 days. The plant extract (at the tested doses of 200 and 400 mg/kg) exhibited a significant hypolipidemiceffect and thus reduced the obesity. The body weight and feed intake was reduced significantly. Treatment of obese animals with the methanolic extract of B. variegata exhibited an increased brain serotonin level and high density lipoprotein with a concomitant decrease in total cholesterol, triglycerides and low density lipo protein. Thus the study indicates that the antiobesity activity of methanolic extract of B. variegata could be attributed to the presence of ?-sitosterol in the stems and the tendency of the extract to reduce lipid profile and elicit the brain serotonin level.